Relatively Poor Survival of Mucinous Ovarian Carcinoma in Advanced Stage: A Systematic Review and Meta-analysis. Issue 4 (1st May 2017) - Simons, Michiel; Massuger, Leon; Bruls, Jolien; Bulten, Johan; Teerenstra, Steven; Nagtegaal, Iris
Abstract : Objective: Overall, patients with mucinous ovarian carcinoma (MOC) are considered to have a better prognosis compared with the whole group of nonmucinous carcinomas. However, some studies indicate that patients with advanced-stage MOC might have a worse prognosis than those with advanced-stage serous ovarian carcinoma (SOC). We carried out a systematic review and meta-analysis of the current literature. Materials and Methods: A comprehensive literature search was carried out identifying 19 articles that compare survival of patients with MOC and patients with SOC. Meta-analyses were performed for risk ratio (RR) and hazard ratio (HR) for all International Federation of Gynecology and Obstetrics stages together, as well as for early- and advanced-stage diseases separately. Results: Overall, patients with MOC showed a lower risk of dying within 5 years (RR, 0.67; 95% confidence interval [CI], 0.64–0.69; n = 45 333) and a longer survival (HR, 0.66; 95% CI, 0.58–0.75; HR, 0.88; 95% CI, 0.78–0.98, for univariate and multivariate analyses, respectively; n = 5540) compared with those with SOC. In contrast, in advanced-stage (International Federation of Gynecology and Obstetrics stages III and IV) disease, patients with MOC have a higher risk of dying within 5 years (RR, 1.15; 95% CI, 1.13–1.17; n = 36 113) and a shorter survival (HR, 1.82; 95% CI, 1.71–1.94; n = 19 907). Conclusions: Patients with advanced-stage MOC have a significantly worse prognosis compared with patients with SOC, whereas in early stage, the prognosis of patients with MOC is better.